Risk of intraocular pressure elevation associated with triamcinolone acetonide administration via different routes in macular edema: a systematic review and network meta-analysis of randomized controlled trials - Kexin Liu; Jinyang Yi; Juan Xu; Li Zhong; Na Su (BMC Ophthalmology)
Abstract Purpose The local application of triamcinolone acetonide (TA) in patients with macular edema (ME) is off-label and the data are limited. We designed a systematic review and network meta-analysis to compare risk of intraocular pressure (IOP) elevation among TA for different routes of administration used by patients diagnosed with macular edema. Methods We obtained data from the PubMed, Medline, Embase, and Cochrane Central Register of Controlled Trials for randomized controlled trials (RCTs). The outcome was IOP at 4, 12 or 24 weeks. We performed random-effects model and consistency model in the Bayesian framework with the multinma package in R. The GRADE was accorded for assess the evidence. Results A total of 1138 citations were identified by our search, of which 16 RCTs enrolled 834 eyes (575 patients). The network showed that TA administration via different local routes and placebo were no significant differences in either pairwise or network estimates at the 4th week. IVTA (intravitreal triamcinolone acetonide) was associated with a statistically significant higher IOP at the 12th week compared to STiTA (sub-Tenon’s infusion of triamcinolone acetonide) (MD: 1.67, 95% CI: 0.25 to 3.15, P < 0.05). IVTA, SCTA (suprachoroidal triamcinolone acetonide) and STiTA were both exhibited a statistically significant variance in IOP compared to placebo at the 24th week [(MD: 1.35, 95% CI: 0.23 to 2.30, P < 0.05), (MD: 2.42, 95% CI: 0.19 to 4.53, P < 0.05), (MD: 1.31, 95% CI: 0.02 to 2.49, P < 0.05)]. The probabilities of rankings and SUCRA showed that, at 4 and 12 weeks of follow-up, IVTA posed the highest risk of IOP elevation, while at the 24-week mark, SCTA exhibited the highest risk. In addition, RITA (retrobulbar injections triamcinolone acetonide) was shown to be safer. Conclusion For the increased risk of IOP, we recommend that treatment within 4 weeks is safe. Nevertheless, it is advisable to exercise caution when administering IVTA, STiTA, SCTA beyond a duration of 12 weeks, due to the potential risk of IOP elevation. RITA emerged as the safest injection route in the treatment of macular edema in terms of IOP risk. However, more high-quality randomized controlled trials will be necessary to further confirm this. Systematic review registration PROSPERO, CRD42022366513. https://www.crd.york.ac.uk/prospero/#recordDetails . Clinical trial number Not applicable